A reply to Thomas Mulligan's “critique of Milton Friedman's essay ‘The Social Responsibility of Business to Increase Its Profits’” - Shaw, Bill (Journal of business ethics, 1988)
Professor Thomas Mulligan undertakes to discredit Milton Friedman's thesis that “The Social Responsibility of Business Is to Increase Its Profits.” He attempts to do this by moving from Friedman's paradigm characterizing a socially responsible executive as willful and disloyal to a different paradigm, i.e., one emphasizing the consultative and consensus-building role of a socially responsible executive. Mulligan's critique misses the point, first, because even consensus-building executives act contrary to the will of minority shareholders, but even more importantly, because he assumes that the mandate of a shareholder majority brings legitimacy to efforts of corporate managers to utilize corporate wealth in solving social problems. It is the role of our democratic institutions to deal with national agenda issues such as inflation, unemployment, and pollution, not that of the private sector. Corporations and private individuals do have a role to play in enhancing the quality of the human environment, however, and the author suggests a coherent means of developing that role in an effort “rescue” corporate social responsibility from Mulligan no less than from Friedman.